АДАБИЙ АЛОҚАЛАР – АДАБИЙ ЖАРАЁН ТАҚОЗОСИ (Ўзбек ва қорақалпоқ адабий алоқалари мисолида) - Қурамбоева, Г. (SCIENCE and SOCIETY, 2022)
The article is devoted to Uzbek and Karakalpak literary relations.Forms of literary relations are discussed.The experience of Karakalpak and Uzbek artistic poets and writers is analyzed in exchanging themes and creating literary categories.
Keywords: literary relations; literary influence; theme; form; image; plot; literary category; genre; conflict; literary tradition; national flavor